2016
DOI: 10.1007/s00417-016-3365-3
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing biomechanical parameters of the cornea with glaucoma severity in open-angle glaucoma

Abstract: Before interpreting corneal biomechanical parameters, it seems important to adjust the measured data for their underlying influencing factors. Glaucoma patients with lower adjusted CH and CRF probably have more advanced disease and should, therefore, be treated more aggressively and monitored more carefully and frequently.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
27
0
8

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 40 publications
4
27
0
8
Order By: Relevance
“…) and the severity of the disease (Pillunat et al. ). Recent studies with the Corvis ST showed a reduced deformability of the cornea in glaucoma patients, even after adjusting for IOP and CCT (Salvetat et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…) and the severity of the disease (Pillunat et al. ). Recent studies with the Corvis ST showed a reduced deformability of the cornea in glaucoma patients, even after adjusting for IOP and CCT (Salvetat et al.…”
Section: Discussionmentioning
confidence: 99%
“…) as well as the severity of the disease (Pillunat et al. ). The second one is the Corvis ST (Corneal visualization Scheimpflug Technology, Oculus GmbH, Weztlar, Germany), where the response of the cornea to an air pulse is monitored using an ultra‐high‐speed Scheimpflug camera.…”
Section: Introductionmentioning
confidence: 99%
“…Glaucoma severity was classified as mild (MD < 6.00 dB), moderate (12 dB > MD ≥6 dB), and severe (MD ≥12 dB) based on the MD [24][25][26][27]. Therefore, POAG patients were categorized into 3 subgroups of different severity level, of which 92 were classified as mild, 56 as moderate, and 92 as severe.…”
Section: Comparison Of Clinical Parameters Of Poag Patients Stratifiementioning
confidence: 99%
“…15,16 Ayrıca, KH ve KRF'nin keratokonus hastalarında, psödofakik gözlerde, Fuchs kornea distrofisinde, primer açık açılı glokom ve normal basınçlı glokom hastalarında daha düşük olduğu gösterilmiştir. [19][20][21][22] Akromegali hastalarında korneanın biyomekanik özelliklerinin OCA ile değerlendirildiği önceki çalışmalar incelendiğinde, Özkök ve ark. ile Altınkaynak ve ark., KH ve KRF değerlerini akromegali hastalarında anlamlı olarak yüksek bulur iken; Şen ve ark., KH ve KRF değerlerini akromegali hasta grubunda daha yüksek ölçmüş, ancak aradaki farkı istatistiksel olarak anlamlı bulmamışlardır.…”
Section: Bulgularunclassified